2023
DOI: 10.1097/brs.0000000000004786
|View full text |Cite
|
Sign up to set email alerts
|

Does Posterior Cord Compression From the Ligamentum Flavum Influence Clinical Outcomes After Anterior Cervical Discectomy and Fusion?

Abstract: Study design: Retrospective cohort study Objective: To clarify whether outcomes of anterior cervical discectomy and fusion (ACDF) differ according to presence of posterior cord compression from the ligamentum flavum (CCLF) Summary of background data: Although ACDF effectively addresses anterior cord compression from disc material and bone spurs, it cannot address posterior compression. Whether ACDF could res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[7][8][9] Literature on the surgical care of CSM does not commonly differentiate the outcome by the cord syndrome involved, and so at the current state of practice evidence, it remains professionally acceptable to treat a posterior cord syndrome anteriorly. 10,11 A recent publication from Korea 12 found that posterior indentations of the cord from ligamentum flavum hypertrophy were not consistently relieved by anterior surgery and so that pathoanatomy argues for a posterior approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Literature on the surgical care of CSM does not commonly differentiate the outcome by the cord syndrome involved, and so at the current state of practice evidence, it remains professionally acceptable to treat a posterior cord syndrome anteriorly. 10,11 A recent publication from Korea 12 found that posterior indentations of the cord from ligamentum flavum hypertrophy were not consistently relieved by anterior surgery and so that pathoanatomy argues for a posterior approach.…”
mentioning
confidence: 99%
“…A recent publication from Korea 12 found that posterior indentations of the cord from ligamentum flavum hypertrophy were not consistently relieved by anterior surgery and so that pathoanatomy argues for a posterior approach.…”
mentioning
confidence: 99%